Solid-state quantum computing proceedings of the 2nd International Workshop on Solid-State Quantum Computing and Mini-School on Quantum Information Science : Taipei, Taiwan, 23-27 June 2008 / editors, Hsi-Sheng Goan, Yueh-Nan Chen ; sponsoring organizations, National Science Council, Taiwan [and others] - Goan, Hsi-Sheng; Chen, Yueh-Nan (AIP conference proceedings, 2008)
"The IWSSQC 2008 covered all aspects of solid-state implementations for quantum information processing, and topics that were addressed included both theoretical and experimental attempts. The specific topics covered in this proceedings include superconducting circuit QED, quantum measurement of solid-state qubits, entanglement in solid-state devices, semiconductor donor spin quantum computing, decoherence and disentanglement in quantum open systems, and mesoscopic electron transport. It provides a unique opportunity for experts and beginners to gain insight into the rapidly growing field of Quantum Information Science. It is also useful as a reference book for graduate students and researchers in Physics and Engineering. Readership: Researchers and graduate students in Physics and Engineering; especially in the fields of Quantum Computation and Quantum Information, Solid-State Quantum computing, Quantum Information Processing, Quantum Open Systems, Mesoscopic and Nanostructure Electron Transport." -- publisher's website.